CCR5Δ32 in Brazil: Impacts of a European Genetic Variant on a Highly Admixed Population - Kulmann-Leal, Bruna; Ellwanger, Joel Henrique; Chies, José Artur Bogo (Frontiers in Immunology, 2021)
The genetic background of Brazilians encompasses Amerindian, African, and European components as a result of the colonization of an already Amerindian inhabited region by Europeans, associated to a massive trade of slaves from Africa. Other migratory flows introduced into the Brazilian population genetic components from Asia and the Middle East. Currently, Brazil has a highly admixed population and, therefore, the study of genetic factors in the context of health or disease in Brazil is a challenging and remarkably interesting subject. This phenomenon is exemplified by the genetic variant CCR5Δ32, a 32 base-pair deletion in the CCR5 gene. CCR5Δ32 originated in Europe, but the time of origin as well as the selective pressures that allowed the maintenance of this variant and the establishment of its current frequencies in the different human populations is still a field of debates. Due to its origin, the CCR5Δ32 allele frequency is high in European-derived populations (~10%) and low or even absent in Asian and African native human populations. In Brazil, the CCR5Δ32 allele frequency is intermediate (4-6%) and varies depending on the migratory history of each region. CCR5 is a protein that regulates the activity of several immune cells, also acting as the main HIV-1 co-receptor. CCR5Δ32 genotypes influence CCR5 expression. No CCR5 functional molecule is observed in CCR5Δ32 homozygous individuals. Thus, CCR5Δ32 has particular effects on different diseases. At the population level, the effect that CCR5Δ32 has on European populations may be different as compared to highly admixed populations. Besides less evident due to its low frequency in admixed groups, the effect of the CCR5Δ32 variant may be affected by other genetic traits. Understanding the effects of CCR5Δ32 on Brazilians is essential to predict the potential use of pharmacological CCR5 modulators. Therefore, this study reviews the impacts of the CCR5Δ32 on the Brazilian population, considering infectious diseases, inflammatory conditions, and cancer. Finally, this article provides a general discussion concerning the impacts of a European-derived variant, the CCR5Δ32, on a highly admixed population.